PENGARUH INSENTIF DAN MOTIVASI KERJA TERHADAP KINERJA PENGEMUDI PT. GRAB BIKE KOTA BEKASI - Naufal Hidayatullah; Hotner Tampubolon; Jonny Siagian (Buletin Ekonomi, 2023)
This study aims to investigate the effects of job motivation and incentives on the productivity of Grab Bike drivers in Bekasi City. The decline in the performance of Grab Bike drivers is caused by the provision of incentives that are still very lacking and difficult to obtain. This led drivers to complain that the diamond target for incentives was too high and the incentive income did not match their expectations. The type of research used is quantitative research methods. In order to generate a representative sample that met the researcher's predetermined criteria, non-probability sampling with purposive sampling approach was utilized in this study. The number of samples taken is 150 respondents. This research technique uses primary data obtained from questionnaire data. Then the data analysis was carried out using multiple linear analysis. The results of the study based on the t test showed that there was a positive influence between Incentives and Motivation on the Performance of Grab Bike Drivers. and based on a descriptive analysis of incentives and work motivation, they make a very strong contribution to the performance of Grab Bike drivers. Companies should pay more attention to providing incentives and motivation for drivers considering that incentives and motivation can be used to improve the performance of Grab Bike drivers. Keywords: Incentives, Work Motivation, Grab Bike Driver Performance